CIVILIZED LEGAL JUSTICE: A STUDY OF LEGAL JUSTICE CONSTRUCTION IN INDONESIAN POSITIVE LAW BASED ON ADAB VALUES - Rahmatullah Ayu Hasmiati; Aulia Vivi Yulianingrum; Dea Justicia Ardha (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
This study examines the characteristics of positive legal justice in Indonesia and the use of the concept of adab from the Islamic worldview as an offer to reconstruct legal justice in Indonesia. This research is doctrinal research using inductive-deductive logic using library materials. The data was then analyzed using qualitative methods. The results showed that First, the characteristics of legal justice in Indonesia, which are based on the paradigm of legal positivism, show that the essence of the source of justice comes from written legal norms, namely the law that separates law and morals. In the end, the separation itself is a manifestation of the law of partial justice. Many legal justice ideas have been developed by several legal experts in Indonesia by making efforts to reconstruct positivist legal thought into the context of Indonesian legal thought that reflects the values of justice based on state philosophy and guidelines for the Preamble of the 1945 Constitution,